Liver Repair in Rabbits Using 532 nm Nd:YAG Laser; In Vivo Study - Tanno, Saba Y.; Mahmood, Ali S. (Iraqi Journal of Laser, 2011)
The main goal of this in vivo study was to evaluate the effect of 532nm Q-switched Nd: YAG Laser in combination with Human Serum Albumin 20% concentration (as a welding aid) on the liver tissue repair clinically, and histologically. The animals used in this study were 21 male rabbits divided into three main groups: control group (3 rabbits), conventionally treated group (9 rabbits) and Laser treated group (9 rabbits). Each two main groups (conventional and laser treated) consist of three sub-groups depending on the response evaluation at three different periods. The Laser group was treated using 532nm Q-switched Nd: YAG laser after adding human serum albumin immediately on the incised liver’s tissue. The energy of was 460mJ, and 4Hz frequency and 60-90 second exposure time. Both groups were compared with the control group. The clinical findings emphasized an effective laser technique in treating the incised liver tissues. The histopathological studies showed a marked regenerative capacity followed by a peak of mitosis. From this work it was concluded that this laser soldering technique has great promise, and could potentially reduce morbidity and mortality associated with liver injury.